Penerapan Model Pembelajaran Digital Game Based Learning (DGBL) Pada Mata Pelajaran Matematika Siswa Kelas V - Rerika Landaini Putri; Angel Maria V. K; Hery Setiyawan (Universitas Palangka Raya, 2024)
The lack of interest of fifth grade students in mathematics subjects causes their inability to understand various mathematics subject topics. New discoveries are needed to overcome low learning outcomes and low student interest in mathematics subjects. Thus, the aim of this research is to find out whether the application of the Digital Game Based Learning (DGBL) learning model can improve learning outcomes and student activity levels in mathematics subjects.These findings indicate that Digital Game Based Learning (DGBL) is effective in increasing students' understanding of mathematical concepts and engagement in learning. Therefore, it is recommended that educators consider using digital games as learning aids, especially in subjects that are considered difficult such as mathematics. Implementation of Digital Game Based Learning (DGBL) also requires technological support and training for teachers for optimal implementation.